Olfactory inputs to appetite neurons in the hypothalamus - Donghui Kuang; Naresh K. Hanchate; Chia-Ying Lee; Ashley Heck; Xiaolan Ye; Michidsaran Erdenebileg; Charu Mehta; Md Mehedi Hassan; Manu Setty; Linda B. Buck (Proceedings of the National Academy of Sciences, 2026)
The sense of smell has potent effects on appetite, but the underlying neural pathways remain undefined. Here, we investigated how olfactory signals reach two subsets of appetite-linked (“appetite”) neurons in the hypothalamic arcuate nucleus: Agouti-related peptide (AgRP) neurons, which stimulate appetite, and POMC (pro-opiomelanocortin) neurons, which suppress it. Using polysynaptic viral tracing, we show that AgRP and POMC neurons receive indirect input from partially overlapping but distinct areas of the olfactory cortex, indicating that they process different sets of olfactory information. We also identify different complements of neurons more directly upstream of AgRP and POMC neurons that could relay olfactory cortical signals to the appetite neurons. Single-cell transcriptomics shows heterogeneous expression of neuromodulator receptors among AgRP neurons, suggesting variations in the signals they receive. Integrated viral tracing and RNA localization further reveals selected brain areas where upstream neurons express cognate receptor ligands. Together, these findings outline multiple pathways by which distinct olfactory and modulatory signals are differentially routed to neurons that promote versus inhibit appetite.